STRATEGI KEPALA MADRASAH DALAM PENINGKATAN DIGITALISASI PEMBELAJARAN DI MAN 1 JOMBANG - Perdi Dwi Pranata; Moh. Syamsyul Falah (Jurnal Manajemen Pendidikan, 2026)
This study comprehensively investigates the strategic management of a madrasah head—encompassing formulation, execution, and evaluation—in accelerating digital transformation to escalate academic quality at MAN 1 Jombang. Employing a descriptive qualitative design, data collection relied on in-depth interviews, classroom observations, and curriculum document analysis involving administrators, teachers, and staff. The findings demonstrate leadership success in pioneering a pilot Digital Class project integrated with the "Secolah" Learning Management System (LMS). This modernization is supported by smartboard infrastructure, balanced with strict gadget regulations to maintain a conducive learning environment. Furthermore, the persuasive leadership style effectively triggers a multiplier effect in boosting teachers' digital literacy through peer mentoring schemes, while data-driven monitoring successfully mitigates institutional culture resistance. The academic novelty of this research lies in reconstructing a digital transformational leadership model within a public Islamic school. This model successfully aligns modern technological adaptation with spiritual reinforcement, ensuring that the madrasah’s digital ecosystem develops productively without neglecting the internalization of noble character values among students.